Comparative analysis of facial morphology between Okinawa Islanders and mainland Japanese using three‐dimensional images. Issue 4 (17th May 2014) - Miyazato, Eri; Yamaguchi, Kyoko; Fukase, Hitoshi; Ishida, Hajime; Kimura, Ryosuke
ABSTRACT Objectives Differences in facial height and breadth between Okinawa Islanders and mainland Japanese have been reported in previous craniometric and somatometric studies. This study using three‐dimensional (3D) images aimed to identify more detailed characteristics of facial morphology in each population. Methods Using a hand‐held 3D scanner, we obtained 60 facial surface images each from Okinawa Islanders and mainland Japanese. Twenty‐one landmarks were plotted on a computer and 27 measurements of distances and angles between the landmarks were taken. Statistical analyses such as t test, principal component analysis (PCA), regression analysis, and discriminant analysis were performed to identify sex and regional differences, the patterns of facial features, factors explaining the facial patterns, and other features. Results Okinawa Islanders showed lower facial and nasal heights than mainland Japanese. Furthermore, we identified larger protrusions of the glabella and nasal root in Okinawa Islanders than in mainland Japanese. In the PCA, we observed components of facial shape patterns. These components mainly represented facial size (PC1), facial depth (PC2), the prominence of the glabella and nasal root (PC3), and facial breadth (PC4). We identified that the population difference is strongly associated with PC3. Conclusions This study quantitatively identified differences in the facial morphology between Okinawa Islanders and mainland Japanese using 3D digital images, with special emphases on the differences in the nasal height and the prominence of the glabella and nasal root. Am. J. Hum. Biol. 26:538–548, 2014. © 2014 Wiley Periodicals, Inc.